Proposed Bulacan drug dependents rehabilitation center - Guevarra, Crizaldo S. (Manila : National University, 2016)
"War against drug" is President Duterte's number one advocacy. Starting from the election campaigns up to the present that he is now the president, he did not change his mindset that drugs should be eliminate to the system as much as possible.
Acknowledgement -- Certificate of endorsement -- Approval sheet -- Table of contents -- List of tables -- List of figures -- List of graphs -- Abstract -- Chapter 1. Introduction -- Chapter 2. Review of Related literature -- Chapter 3. Research design -- Chapter 4. Project profile -- Chapter 5. Analysis -- Chapter 6. Schematics.
Includes bibliographical references.
Keywords: REHABILITATION CENTER